Investigation of the Free and Total Thyroxine-binding Capacity of Plasma Proteins in Thyroid Disorders - Bános, Csaba; Takó, József; Fischer, János; Juhász, Jusztina; Sztraka, Ilona; Kapus, István (Nuklearmedizin - NuclearMedicine, 1971)
The results of thyroid function tests have been compared with data on the thyroxine-binding capacity of plasma proteins in hyper-, hypo- and euthyroid cases, the latter including women taking oral contraceptives (Infecundin). It was found that there exists a significant correlation of exponential nature between the in vitro red blood cell 125I-triiodothyronine uptake (RCU) and the free thyroxine-binding capacity of the thyroxine-inding globulin (TBG).